Psalms In/On Jerusalem - Münz-Manor, Ophir; Pardes, Ilana (Perspectives on Jewish texts and contexts (Series), 2019)
This volume explores the ways in which Jerusalem is represented in Psalms - from its position in the context of liturgical and pilgrim songs to its role as metaphor. Jerusalem in the Book of Psalms is the site of scenes of redemption, joy, and celebration of the proximity to God and the house of the Lord. But it is also the quintessential locus of loss, marked by cries over the devastating destruction of the Temple. These two antithetical poles of Jerusalem are expressed in both personal terms as well as within a collective framework. The bulk of the articles are devoted to questions of reception, to the ways in which the geographies of the Book of Psalms have travelled across their native bounds and entered other historical settings, acquiring new forms and meanings.